The Semiotic Monad as a Prefiguration of the Window: Trajectories of Theoretical Imagination in Juri Lotman’s Semiotics of Culture - Šileikaitė, Ieva (Semiotika, 2025)
The article addresses the problem of whether the figurative expressions appearing unexpectedly in Juri Lotman’s metalanguage should be seen as integral to his theoretical system rather than incidental. To explore this issue, the study examines two seemingly unrelated descriptions of meaning mechanisms from Lotman’s late period – the semiotic monad (1989) and the window (1992) – which are relatively minor, brief, and appear in his texts from different years. In seeking a meaningful connection between these descriptions, the article aims to conceptualize the semiotic monad from the perspective of figurativity, interpreting its “entrance” and “exit” mechanisms as a prefiguration of the window. The interpretation proceeds in three steps: (1) presenting the structure of the semiotic monad; (2) clarifying the connection between the aforementioned descriptions and situating it within the broader context of Lotman’s spatial mode of thought; (3) discussing how the interpretation of the semiotic monad engages with Gottfried Wilhelm Leibniz’s philosophical concept of the “windowless” monad. The study reveals a trajectory of Lotman’s theoretical imagination that moves from abstract reflection on complex semiotic processes toward a more tangible and visually articulated form.